2002
DOI: 10.1097/00000542-200202000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Can Assessment for Obstructive Sleep Apnea Help Predict Postadenotonsillectomy Respiratory Complications?

Abstract: The data suggest, but do not prove, that preoperative nocturnal oximetry could be a useful preoperative test to identify children who are at increased risk for postoperative respiratory complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
184
6
10

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 189 publications
(211 citation statements)
references
References 1 publication
8
184
6
10
Order By: Relevance
“…[12][13][14] Patients younger than three years, with Down syndrome or with co-morbidities, such as asthma and neuromuscular diseases, as well as those with severe obstructive sleep apnea syndrome are at increased risk for complications after tonsillectomy. 14,15 Researchers have shown that half of the medical interventions performed to treat respiratory morbidity in children undergoing tonsillectomy are needed within the first postoperative hour. 15 Furthermore, researchers showed that children with obstructive sleep apnea appear to have increased sensitivity to opioids, and respiratory complications after adenotonsillectomies are often seen within two hours of opioid administration.…”
Section: Résumémentioning
confidence: 99%
“…[12][13][14] Patients younger than three years, with Down syndrome or with co-morbidities, such as asthma and neuromuscular diseases, as well as those with severe obstructive sleep apnea syndrome are at increased risk for complications after tonsillectomy. 14,15 Researchers have shown that half of the medical interventions performed to treat respiratory morbidity in children undergoing tonsillectomy are needed within the first postoperative hour. 15 Furthermore, researchers showed that children with obstructive sleep apnea appear to have increased sensitivity to opioids, and respiratory complications after adenotonsillectomies are often seen within two hours of opioid administration.…”
Section: Résumémentioning
confidence: 99%
“…5 The inclusion criteria were: 1) a sleep study documenting severe OSAS; 2) adenotonsillectomy within six months prior to surgery; and 3) extubation in the operating room at the end of surgery. The diagnostic criterion for severe OSAS was an abnormal sleep study defined, in our institution and elsewhere, 8 by an obstructive apnea and hypopnea (OAH) index > 5 events·hr -1 .…”
Section: Patient Selection Criteriamentioning
confidence: 99%
“…Details of our sleep study recording systems have been published elsewhere. [9][10][11][12] Although the studies were analyzed for several variables, 5 only the OAH index and the preoperative saturation nadir (preSaO 2 nadir) are reported. The preSaO 2 nadir was defined as the minimum hemoglobin oxygen saturation regardless of duration and was validated by visual inspection of a computerized data record.…”
Section: Chart Review and Study Parameters Diagnostic Criteria For Osasmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, access may be limited by availability of sleep laboratories, resources and lack of consensus on interpretation of PSGs. The overnight pulse oximetry in place of formal PSG is not only cost effective, but also beneficial for identifying the so called 'normal child with severe OSA' who is otherwise difficult to identify with the history and examination alone [7]. There are two parameters of interest that normally give an indication as to whether the child has OSA or not -the saturation nadir (min SpO2 dip) and the Oxygen Desaturation Index (ODI).…”
Section: Pulse Oximetry and Polysomnography (Psg)mentioning
confidence: 99%